CVOT Summit Report 2023: new cardiovascular, kidney, and metabolic outcomes - Schnell, Oliver; Barnard-Kelly, Katharine; Battelino, Tadej; Ceriello, Antonio; Larsson, Helena Elding; Fernández-Fernández, Beatriz; Forst, Thomas; Frias, Juan-Pablo; Gavin, James R; Giorgino, Francesco; Groop, Per-Henrik; Heerspink, Hiddo J L; et al. (Cardiovascular diabetology, 2024)
The 9th Cardiovascular Outcome Trial (CVOT) Summit: Congress on Cardiovascular, Kidney, and Metabolic Outcomes was held virtually on November 30-December 1, 2023. This reference congress served as a platform for in-depth discussions and exchange on recently completed outcomes trials including dapagliflozin (DAPA-MI), semaglutide (SELECT and STEP-HFpEF) and bempedoic acid (CLEAR Outcomes), and the advances they represent in reducing the risk of major adverse cardiovascular events (MACE), improving metabolic outcomes, and treating obesity-related heart failure with preserved ejection fraction (HFpEF). A broad audience of endocrinologists, diabetologists, cardiologists, nephrologists and primary care physicians participated in online discussions on guideline updates for the management of cardiovascular disease (CVD) in diabetes, heart failure (HF) and chronic kidney disease (CKD); advances in the management of type 1 diabetes (T1D) and its comorbidities; advances in the management of CKD with SGLT2 inhibitors and non-steroidal mineralocorticoid receptor antagonists (nsMRAs); and advances in the treatment of obesity with GLP-1 and dual GIP/GLP-1 receptor agonists. The association of diabetes and obesity with nonalcoholic steatohepatitis (NASH; metabolic dysfunction-associated steatohepatitis, MASH) and cancer and possible treatments for these complications were also explored. It is generally assumed that treatment of chronic diseases is equally effective for all patients. However, as discussed at the Summit, this assumption may not be true. Therefore, it is important to enroll patients from diverse racial and ethnic groups in clinical trials and to analyze patient-reported outcomes to assess treatment efficacy, and to develop innovative approaches to tailor medications to those who benefit most with minimal side effects. Other keys to a successful management of diabetes and comorbidities, including dementia, entail the use of continuous glucose monitoring (CGM) technology and the implementation of appropriate patient-physician communication strategies. The 10th Cardiovascular Outcome Trial Summit will be held virtually on December 5-6, 2024 ( http://www.cvot.org ).
Keywords: tepový objem; obezita; kardiovaskulární nemoci; Humans; Heart Failure; Stroke Volume; srdeční selhání; Blood Glucose Self-Monitoring; ledviny; Kidney; lidé; chronická renální insuficience; selfmonitoring glykemie; Blood Glucose; Diabetes Mellitus; Diabetes Mellitus, Type 2; Cardiovascular Diseases; krevní glukóza; Obesity; diabetes mellitus; diabetes mellitus 2. typu; Renal Insufficiency, Chronic